Jami - Algar, Hamid; Oxford Centre for Islamic Studies (New Delhi : Oxford University Press, 2013)
On the life and works of Jami, 1414-1492, Persian poet.
"Oxford Centre for Islamic Studies."
Includes bibliographical references and index.
Keywords: Jāmī, -- 1414-1492 -- Criticism and interpretation